IPS Learning on Natural Environmental Material and Artificial Environment Based on Contextual Teaching And Learning Through Interactive Comic Media - Ninik Indawati; Friorina Tri Puspa Andariana; Delita Pristyoawti (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
This study aims to produce and describe the process of developing interactive comics media for IPS learning material on natural environment and artificial environment based contextual teaching and learning. Researchers developed procedures include 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) initial field trials, 7) field trials, 8) product revisions, and 9) final products. Data analysis by quantitative, data obtained from material expert, media expert, teacher and student response questionnaires. Based on the data analysis, it can be concluded that the feasibility of interactive comic media is in the appropriate category with an average 98.2% from material experts get average 94.2% from media experts, while the teacher gets average score 97.9%. Students' responses to interactive comic media in a limited field trial with 10 students obtained 95% with valid category and field trial with 34 students obtained average score of 90%.